Transradial approach for diagnostic cerebral angiography: first experience in a social security hospital - Saal-Zapata, Giancarlo (2021)
Transradial approach for cerebral diagnostic angiography is gaining territory in the neuroendovascular field for diagnostic and therapeutic procedures. Less complication rates, less hospital stay and patient comfort are some features of this approach. Nevertheless, the transition from the classic femoral approach to the radial approach is difficult to achieve in institutions with established protocols. We present our initial experience using the transradial approach for cerebral diagnostic angiography performed successfully achieving catheterization of the supra-aortic vessels.